2017
DOI: 10.1080/07435800.2017.1292523
|View full text |Cite
|
Sign up to set email alerts
|

The correlation between insulin-like growth factor 1 (IGF-1) and novel adipocytokines in postmenopausal women: A population-based study

Abstract: The adipocytokines and insulin-like growth factor 1 (IGF-1) are involved in insulin resistance, the cardiometabolic syndrome, and atherosclerosis. Therefore, investigating the relationship between circulating levels of the novel adipocytokines and IGF-1 is worthwhile. The correlation between IGF-1, visfatin, and omentin-1 has not been adequately investigated. In a population-based study, 324 postmenopausal women were randomly selected. Circulating IGF-1, visfatin, omentin-1, adiponectin, and high-sensitivity C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 35 publications
1
1
0
Order By: Relevance
“…This present study result showed that there was no significant correlation between IGF-1 and adiponectin levels. This finding is in line with several previous studies, where there was also no significant correlation between IGF-1 and adiponectin levels in healthy postmenopausal females and healthy elderly men [13,27]. However, correlation studies between adiponectin and IGF-1 levels still show inconsistent results.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This present study result showed that there was no significant correlation between IGF-1 and adiponectin levels. This finding is in line with several previous studies, where there was also no significant correlation between IGF-1 and adiponectin levels in healthy postmenopausal females and healthy elderly men [13,27]. However, correlation studies between adiponectin and IGF-1 levels still show inconsistent results.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, this study aimed to find out the longterm KD effect on serum adiponectin and IGF-1 levels in mice. A previous study regarding the correlation between adiponectin and IGF-1 showed that there was still an inconsistent association between adiponectin and IGF-1 [13]. Considering the involvement of adiponectin and IGF-1 in the development of several diseases, this study also evaluates the correlation between serum adiponectin and IGF-1 levels.…”
Section: Introductionmentioning
confidence: 97%